Análisis de la insuficiencia de recursos en el pago del aporte complementario por parte de los obligados subsidiarios, que vulnera los derechos del alimentario - Ojeda Sánchez, Alex Eduardo (2022)
This thesis entitled: ¨ANALYSIS OF THE INSUFFICIENCY OF RESOURCES IN THE PAYMENT OF THE COMPLEMENTARY CONTRIBUTION BY THE OBLIGATED SUBSIDIARIES, THAT VULNERATES THE RIGHTS OF THE FOOD ¨, a legal problem that deserves to be transformed to solve and overcome the socio-legal problem of the Organic Code of Childhood and Adolescence in article 5 (130), which refers to those forced to provide food , that when proven before the judge, the subsidiary guarantors are in a critical health condition or lack of economic resources, any duty regarding the needs of the minor will be the responsibility of the defendant parent, who cannot avoid the obligations that by law correspond. The aforementioned law will ensure the rights of both the minor and the subsidiary obligor, preparing and executing contact programs between parents, subsidiary obligors and the minor, through their respective agencies, aimed at achieving a better understanding between them; promoting collective bargaining; and tend to the extrajudicial treatment of collective conflicts that are in the family sphere, which tends to approximate the positions of the parties; and, coordinating the obligations of the parents. The motivation is the need to reform the aforementioned article, which will indicate that all accumulated obligations will return to the defendant father and he will not be able to evade his responsibility by manifesting the cause invoked to guarantee that he assumes the responsibility of providing what by right corresponds to the minor, Given what is expressed in the regulations, the competent authority is not based, where due process is not infringed so as not to violate the rights of the subsidiary obligor, as mentioned in the Political Constitution of the Republic of Ecuador, in its article that stipulates that every person has the right to the free access to justice and effective, impartial and expeditious protection of his rights and interests, subject to the principles of speed and legal certainty; in no case will he be helpless. Failure to comply with judicial resolutions will be sanctioned by law. All this denotes that in our country there is a norm recognized in the Constitution that tends to protect the rights of the subsidiary obligor and of the parents, thus enforcing the obligations of the parent, and being able to find a feasible solution.